Altmetrics – beyond the bibliometrics: a new tool for online attention to the publication (Journal of Forensic Medicine & Toxicology, 2025)
Altmetrics are alternative ways of measuring the reach and impact of research via digital interactions. Unlike traditional citations, they capture real-time engagement across blogs, social media, and online news.
Keywords: platforms; Altmetrics; alternative